Jazzwomen : Conversations with Twenty-One Musicians - Enstice, Wayne, 1943- (Book collections on Project MUSE., 2004)
""Their conversations range far beyond the biographical-to their feelings, motivations, musical approaches, and attitudes. These women were obviously comfortable with their questioners. [Enstice and Stockhouse] came prepared, having delved deeply into the music and history of each, bringing them closer to the essence of each musician."" -from the Preface by Cobi Narita and Paul Ash""Jazzwomen includes many artists who are not covered in earlier books and also reveals new information about artists who are. In addition, the interview format used in Jazzwomen provides the reade.